Pelatihan Pemasaran Digital Bagi Calon Wirausahawan di Panti Sosial Bina Remaja Taruna Jaya Jakarta Timur - Santosa, Wahyuningsih; Octaviani, Dian; Astrid Maria Esther; Arrum Anggraini Darmawan; Rayhan Fadillah; Haryanto, Jennifer Victoria Astari (Politeknik Piksi Ganesha Indonesia, 2025)
This Community Service (PkM) activity aims to educate aspiring entrepreneurs at the Taruna Jaya 1 Youth Social Institution about the importance of digital marketing strategies for achieving success in the digital era. Entrepreneurs, including MSMEs, need to leverage technology and digital platforms to enhance visibility, reach a broader market, and build stronger customer relationships. A participatory educational method was employed, encouraging active discussions. As a result, participants understood practical steps such as identifying target markets, building a strong online presence, utilizing content marketing and social media, and the importance of evaluating digital marketing strategies. With proper implementation, entrepreneurs can increase competitiveness and achieve sustainable business growth.